Low-Coherence Reflectometry for Refractive Index Measurements of Cells in Micro-Capillaries - Carpignano, Francesca (Sensors (Basel), 2016)
The refractive index of cells provides insights into their composition, organization and function. Moreover, a good knowledge of the cell refractive index would allow an improvement of optical cytometric and diagnostic systems. Although interferometric techniques undoubtedly represent a good solution for quantifying optical path variation, obtaining the refractive index of a population of cells non-invasively remains challenging because of the variability in the geometrical thickness of the sample. In this paper, we demonstrate the use of infrared low-coherence reflectometry for non-invasively quantifying the average refractive index of cell populations gently confined in rectangular glass micro-capillaries. A suspension of human red blood cells in plasma is tested as a reference. As a use example, we apply this technique to estimate the average refractive index of cell populations belonging to epithelial and hematological families.